2015
DOI: 10.1038/srep08599
|View full text |Cite
|
Sign up to set email alerts
|

Rate-dependent phase transitions in Li2FeSiO4 cathode nanocrystals

Abstract: Nanostructured lithium metal orthosilicate materials hold a lot of promise as next generation cathodes but their full potential realization is hampered by complex crystal and electrochemical behavior. In this work Li2FeSiO4 crystals are synthesized using organic-assisted precipitation method. By varying the annealing temperature different structures are obtained, namely the monoclinic phase at 400°C, the orthorhombic phase at 900°C, and a mixed phase at 700°C. The three Li2FeSiO4 crystal phases exhibit totally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 43 publications
6
53
0
Order By: Relevance
“…Figure B shows the refined crystal structures, in which Ti incorporation effectively decreases the Li–Li hoping distance between the adjacent LiO 4 tetrahedron that favors facile Li‐ion movement in the sample. Many of the previous studies report that the monoclinic structure of LFSO/C has been changed to a stable orthorhombic phase with better electrochemical properties after a few charge‐discharge cycles . This work reports a direct preparation of the stable orthorhombic structure ( Pmn 2 1 ) for bare and doped LFSO/C samples to obtain the best electrochemical performance with better cycling.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Figure B shows the refined crystal structures, in which Ti incorporation effectively decreases the Li–Li hoping distance between the adjacent LiO 4 tetrahedron that favors facile Li‐ion movement in the sample. Many of the previous studies report that the monoclinic structure of LFSO/C has been changed to a stable orthorhombic phase with better electrochemical properties after a few charge‐discharge cycles . This work reports a direct preparation of the stable orthorhombic structure ( Pmn 2 1 ) for bare and doped LFSO/C samples to obtain the best electrochemical performance with better cycling.…”
Section: Resultsmentioning
confidence: 91%
“…The absence of the peak located at 2 θ = 31.6°, corresponding to the (112) plan of the monoclinic phase and the low‐intensity ratio of the peaks at 2 θ = 33.22/33.70° corresponding to (210)/(020) planes in the XRD pattern demonstrated that the prepared samples assume orthorhombic structure with the Pmn 2 1 space group. It is very difficult to differentiate the orthorhombic phase with the Pmn 2 1 space group from the monoclinic phase with P 2 1 / n (coexisting with minor differences).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, quality has been recognized by the Raman spectrum and nitrogen adsorption and desorption experiment for the as-prepared LFS@ESM, as shown in Figure 2c. From the Raman spectrum, two peaks are pointed out one is for order graphite (G) peak at 1586 cm −1 and another one is for disorder (D) peak at 1340 cm −1 , which were aroused due to E2g zone-center and A1g zone-edge mode vibration [40]. The degree of graphitization of LFS@ESM depends on the ratio of integrated intensity of D and G-band (ID/IG) is equal to 0.94, the value less than one indicates that higher graphitized carbon (better quality).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there are great interests in upgrading anode performance by doping TiN into anode matrix. Anchoring of TiN nanoparticles to graphene layers not only promotes the electrical conductivity along caxis, but also suppresses the agglomeration of graphene sheets, resulting in the formation of a exible porous texture [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%